Panel summary: Accessing precision therapies for children and youth in Canada - Gauvreau, C; Wight, L; Subasri, M; Wilson, MG; Denburg, A (My University, 2021)
A thematic summary of what was learned from the citizen panel on accessing precision therapies for children and youth in Canada. about the problem (and its causes), elements of a potentially comprehensive approach for addressing it, key implementation considerations, and possible next steps.
Keywords: precision therapies; children; youth; Canada